Self-objectification, body image disturbance, and eating disorder symptoms in young Australian children - Jongenelis, M.; Byrne, S.; Pettigrew, Simone (Elsevier, 2014)
Self-objectification has been examined extensively in adult populations. Despite theoretical evidence suggesting that children may also be vulnerable to experiencing self-objectification, whether children do self-objectify has not been determined. Accordingly, the present study examined the degree to which children self-objectify. The prevalence of body image and eating disturbances in this population, and the relationship between self-objectification and these disturbances, were also investigated. Results from over 250 boys and girls aged 6–11 years revealed that young girls report levels of self-objectification that are similar to those observed among older girls and women. Self-objectification was also found to be meaningfully related to body image and eating disturbances in children. A significant proportion of children reported body dissatisfaction and a minority engaged in disordered eating behaviours in the four weeks prior to the assessment. These results suggest that children may be at risk of experiencing the negative psychological outcomes associated with self-objectification.